PENGARUH FOOD QUALITY, DINING ATMOSPHERE DAN KESESUAIAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi pada Kribo Coffee Jl. Joyo Agung No 53 B, Tlogomas Kec. Lowokwaru, Kota Malang) - Imas Maulani; M. Hufron; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted to determine the effect of food quality, dining atmosphere and price suitability on customer satisfaction on Kribo Coffee consumers who are located at Jl. Joyo Agung No 53 B, Tlogomas Kec. Lowokwaru, Malang City. The method used is explanatory research that aims to explain the position of each variable and its effect between one variable with another variable, and the source of the data used is primary data by distributing Likert-scale kusieoner to Kribo Coffee consumers. The sample calculation in this study uses the Slovin formula which produces 80 respondents. The results of this study are the variables of food quality, dining atmosphere and price suitability simultaneously and partially affect the customer satisfaction. Keywords: food quality, dining atmosphere, price suitability and customer satisfaction.